Design of a rhenium-decorated mesoporous nickel phyllosilicate-derived Ni–Re/MCM-41 catalyst for efficient hydrogenation of levulinic acid to γ-valerolactone - Maneewong, Yupawan; Lakhani, Pratikkumar; Ratchahat, Sakhon; Sakdaronnarong, Chularat; Limphirat, Wanwisa; Rungtaweevoranit, Bunyarat; Assabumrungrat, Suttichai; Khosukwiwat, Kanyanat; Choojun, Kittisak; Sooknoi, Tawan; Tomishige, Keiichi; Srifa, Atthapon (My University, 2026)
Herein, Ni and NiRe catalysts supported on mesoporous MCM-41 were synthesized through ammonia evaporation (AE) and impregnation (IM) routes to explore structure–activity correlations in the hydrogenation of levulinic acid (LA) to γ-valerolactone (GVL). The AE-derived nickel phyllosilicate (Ni-PS) framework provided strong interactions through Ni–O–Si linkages, leading to high dispersion and stabilization of Ni species. Incorporation of Re significantly improved reducibility, hydrogen activation, and the balance between acidic and metallic sites, resulting in enhanced catalytic efficiency. The optimized NiRe-PS catalyst exhibited a uniform nanostructure, strong Ni–Re synergy, and the highest metallic Ni fraction, which collectively promoted superior activity and stability. Under mild conditions (140 °C, 10 bar H2), NiRe-PS achieved complete LA conversion and ∼96% GVL yield within 4 h, with a turnover frequency of 26.3 h−1 (160 °C, 10 bar H2) and with an apparent rate constant of 0.0059 min−1. Mechanistic and isotopic investigations confirmed that both molecular and solvent-derived hydrogen contributed to the hydrogenation pathway. The exceptional activity, recyclability, and structural robustness of NiRe-PS demonstrate the potential of phyllosilicate-based bimetallic systems as efficient, non-noble catalysts for sustainable biomass valorization.